Illocutionary Acts Used by the Main Character in “The Menu” Movie - Satyawati, Made Sri (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 31 No 2 (2024): SeptemberDO - 10.24843/ling.2024.v31.i02.p08, 2024)
Movies serve as a media for examining illocutionary behaviors, that for instances where speaker intentions may lead to misunderstandings. Characters in movies convey their thoughts through dialogues, and given the diverse interpretations people have, it becomes crucial to discern the intended messages through the study of illocutionary acts. This study examines the types of illocutionary act and the context of situations underlying the meaning from the main character utterances in “ The Menu” movie. Observation method and note – taking technique were used in order to collect the data while to analyze the data the descriptive qualitative method was applied. The data were analyzed with Searle’s illocutionary act theory and context of situation theory by Hallday and Hasan. The result showed that every types of illocutionary act are found in “The Menu” movie, they are assertive, directive, commissive, expressive and declarations and all of the three components of context of situation namely field, tenor and mode are found in each types of illocutionary acts in “The Menu” movie.